2008
DOI: 10.1038/jcbfm.2008.20
|View full text |Cite
|
Sign up to set email alerts
|

Arctic Ground Squirrel (Spermophilus Parryii) Hippocampal Neurons Tolerate Prolonged Oxygen—Glucose Deprivation and Maintain Baseline ERK1/2 and JNK Activation Despite Drastic ATP Loss

Abstract: Oxygen-glucose deprivation (OGD) initiates a cascade of intracellular responses that culminates in cell death in sensitive species. Neurons from Arctic ground squirrels (AGS), a hibernating species, tolerate OGD in vitro and global ischemia in vivo independent of temperature or torpor. Regulation of energy stores and activation of mitogen-activated protein kinase (MAPK) signaling pathways can regulate neuronal survival. We used acute hippocampal slices to investigate the role of ATP stores and extracellular si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
58
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 42 publications
1
58
0
Order By: Relevance
“…Dave et al 2006;Christian et al 2008), and estivation (Smith 1930;Smith 1931). Several authors (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dave et al 2006;Christian et al 2008), and estivation (Smith 1930;Smith 1931). Several authors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The diapausing Caenorhabditis elegans (dauer larva; reviewed in Honda and Honda 2002) is resistant to a wide range of environmental stresses. Recent studies have shown also that brain and liver tissues of hibernating squirrels are characterized by increased oxidative stress resistance (Lindell et al 2005;Dave et al 2006;Christian et al 2008). An adaptive response to oxidative stress often includes increased synthesis and/or activity of intracellular antioxidant enzymes, which can protect cellular macromolecules from potentially lethal stress-induced damage.…”
mentioning
confidence: 99%
“…Liver and intestine isolated from the thirteen-lined ground squirrel during inter-bout arousal resist I/R injury; however, tolerance is lost or decreased when tissue is obtained from animals during the summer season (Kurtz et al, 2006; Lindell et al, 2005). By contrast, in AGS, tolerance to cerebral I/R in acute hippocampal slices is actually greater during the summer season than during winter inter-bout euthermy; where, only during inter-bout euthermy is any difference noted between active and hibernating ground squirrels (Christian et al, 2008). In other species, the state of hibernation seems to enhance tolerance relative to active (euthermic) animals and rats, although, as bath temperature is decreased, tolerance of brain slices from active animals approaches the degree of tolerance observed in slices from hibernating animals (Frerichs and Hallenbeck, 1998).…”
mentioning
confidence: 88%
“…However, P aO 2 falls significantly during arousal from hibernation (Ma et al, 2005). Whether resistance to ischemic or hypoxic injury depends on the hibernation season, and thus seasonal expression of a hibernation phenotype, remains a matter of debate and may depend on the tissue and species studied (Christian et al, 2008;Kurtz et al, 2006). Here we provide a brief overview of hibernation and review evidence for resistance to ischemia/reperfusion (I/R) injury in hibernating species with emphasis on the arctic ground squirrel (AGS), Urocitellus parryii.…”
Section: Anoxic Survival Mechanisms Also Reduce Ros Damagementioning
confidence: 99%
See 1 more Smart Citation